2001
DOI: 10.1006/viro.2001.0972
|View full text |Cite
|
Sign up to set email alerts
|

Broad Distribution of the JC Virus Receptor Contrasts with a Marked Cellular Restriction of Virus Replication

Abstract: To investigate the early events of JC virus (JCV) infection, including attachment, penetration, transport to the nuclei, and replication of the virus, we analyzed the susceptibility of 15 different cell lines to infection using a semiquantitative polymerase chain reaction (PCR) assay, in situ hybridization, laser scanning confocal microscopy, and a viral replication assay. The cell lines examined were human permissive and nonpermissive cells as well as cells of monkey and mouse origin. JCV entry into the nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 39 publications
1
54
1
Order By: Relevance
“…We had previously shown that wtVLPs are transported to the nucleus of various other cell types (19). These observations indicate that wtVLPs are able to enter the nucleus of both permissive and nonpermissive cells, and, together with the results of previous studies (4,19), they suggest that the neurotropism of JCV is attributable to intranuclear mechanisms such as DNA replication, transcription, or virus assembly.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We had previously shown that wtVLPs are transported to the nucleus of various other cell types (19). These observations indicate that wtVLPs are able to enter the nucleus of both permissive and nonpermissive cells, and, together with the results of previous studies (4,19), they suggest that the neurotropism of JCV is attributable to intranuclear mechanisms such as DNA replication, transcription, or virus assembly.…”
Section: Discussionsupporting
confidence: 55%
“…The cells were then examined with a laser-scanning confocal microscope (Olympus, Tokyo, Japan). Preparation of VLPs-VLPs composed of wtVP1 or ⌬NLS-VP1 were prepared as previously described (19), with slight modifications. The expression plasmids for wtVP1 and ⌬NLS-VP1 were separately introduced into competent E. coli BL21(DE3)/pLys cells (Stratagene, La Jolla, CA) by transformation, and expression of the recombinant proteins was induced by incubation of the cells for 4 h at 30°C with 1 mM isopropyl-␤-D-thiogalactopyranoside.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemagglutin (HA) Assay-Measurement of JCV titer was based on HA of human type O erythrocytes as described previously (35). Human blood was supplied from the Hokkaido Red Cross Blood Center.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were fixed for 3 min in 100 % methanol at 220 uC. Non-specific binding sites were blocked with 1 % BSA and the cells were incubated with a mAb to SV40 TAg (PAb416; Calbiochem), which recognizes the epitope corresponding to aa 83-128, and a polyclonal antibody to JCV VP1 (Suzuki et al, 2001) overnight at 4 uC. Immune complexes were visualized by incubation with AlexaFluor 488-conjugated secondary antibodies (Invitrogen) for 1 h at room temperature.…”
mentioning
confidence: 99%